Accounting Training Behavior to Develop the Profession of Accounting Professionals in Thailand - Limoransuksakul, Manyad; Sueannoi, Thanomsak (Rajapark Journal, 2024)
This research aimed to study the level of opinions on factors influencing the decision to enroll in accounting training courses among accounting professionals and to validate a causal relationship model with empirical data. A quantitative research approach was employed. The population consisted of accounting professionals in Thailand, with an unknown population size. The sample size was 404 individuals, selected through a convenience sampling method. The research findings revealed that most of the respondents were female, under 25 years old, held a bachelor’s degree, had a monthly income of less than 30,000 baht, and had 1-10 years of accounting experience. They were interested in professional accounting development programs offered on weekends (Saturday and Sunday) through online platforms. Regarding the level of opinions, financial rewards, professional recognition, and professional training positively influenced attitudes. In terms of the relationships between variables, attitudes, social values, and perceived continuous professional development had a statistically significant influence on the intention to enroll in training programs at the 0.05 level. However, perceived continuous professional development did not influence the decision to enroll in training programs. The model fits the data well.